Development of applied physics instructional materials for the technology and engineering specialization - Masriani Masriani; Nurhasan Syah; Waskito Waskito; Kasman Rukun; Abdul Habib Arrasyidi Desky (Lentera Negeri, 2026)
This study was motivated by the limited integration of Android-based mobile devices into learning activities and the low learning achievement of vocational students in Temperature and Heat and Thermodynamics. This study aimed to develop an online Physics module for the Technology and Engineering specialization and examine its validity, practicality, and effectiveness. The study employed a research and development approach using the Instructional Development Institute (IDI) model, consisting of define, develop, and evaluate stages. Product validation involved six experts, comprising three content validators and three design validators. The practicality evaluation involved four Physics teachers and 40 students, while the effectiveness test involved 80 students divided equally into an experimental group (n = 40) and a control group (n = 40). Data were collected using validation and practicality questionnaires and a learning-outcome test. The test instrument was piloted outside the research sample, yielding 27 valid items with a Cronbach’s alpha of 0.92; 20 items were selected for the final test. The results showed valid content (Aiken’s V = 0.730) and design (Aiken’s V = 0.705). The module was rated very practical by teachers (83.33%) and practical by students (68.25%). The experimental group achieved an N-Gain of 0.71 (high), compared with 0.29 (moderate) in the control group. These findings indicate that the developed Android-based online Physics module is valid, practical, and potentially effective for supporting Physics learning in vocational Technology and Engineering education.